Analisis Kefasihan Pembelajar Bahasa Korea dalam Membaca Teks Berbahasa Korea - Theresia Avila Rencidiptya Gitanati Firstantin (Universitas Gadjah Mada, 2019)
Fluency in reading is one of the important factors in language learning, especially foreign languages. Fluency in reading can be seen from understanding vocabulary, reading speed, rhythm and expression, also understanding the reading’s contents. Reading fluently is one of the effective learning methods to help for understanding the vocabulary and the content of the text. Reading fluency is needed by Korean leaners when working with Korean stakeholders. This study analyzes the fluency of Korean language learners in reading Korean texts using qualitative descriptive methods. This study found that the learning period and the Korean Language Proficiency Test score of the learner are not always directly assesed to leaner’s fluency in reading. Fluency in reading is also influenced by some factors, such as how much intensity and frequency of learners learn new vocabulary through text, and how instructors provide learning about morphology in how to read a word in Korean.